Nutrients Variability in Soils of the Hill-Valley Transect of NPI Farmlands in Chitwan - Adhikari, K.R.; Lamichhane, S. (NPI Journal of Science and Technology, 2024)
Based on landscape position, soils in plain areas are generally considered to be more fertile than those in adjoining sloping areas of Nepal. This article compares the soil fertility of upland crop areas to those of lowland crop areas of Bharatpur municipality of Chitwan district using soil data from Nepal Polytechnic Institute (NPI). The study employed a rapid test method to analyze surface soil samples for pH, organic matter and available nitrogen, phosphorus, and potassium content. In contrast to the widely held notion, results of soil test in the upland area of Kabilash exhibited superior fertility in most parameters when compared to those in the southern plain areas. Therefore, further and detailed study is warranted to validate the results in the study area.